La inserción laboral y su incidencia en la socialización de las personas con discapacidad física del centro de salud y del gobierno autonomo descentralizado del cantón Zapotillo durante el periodo octubre 2013 – febrero – 2014. Lineamientos alternativos - MONCAYO FLORES, NANCY BEATRIZ (2015)
This research called: THE OCCUPATIONAL AND ITS IMPACT ON socialization of people with physical disabilities HEALTH CENTER AND THE HOME GOVERNMENT DESENTRALIZADO Zapotillo Canton DURING THE PERIOD OCTOBER 2013 - FEBRUARY - 2014.ALTERNATIVE LINES. The central problem under investigation, refers to how the labor market and affects the socialization of people with physical disabilities the Center for Health and the Autonomous Decentralized Government Zapotillo Canton during the period October 2013 - February - 2014. In this thesis the overall objective was: To determine how the labor market influences in the socialization of people with physical disabilities in the Health Center and Decentralized Autonomous Government Zapotillo Canton. The methods used in this research were: the scientific method used to develop the theoretical framework and the analysis of results; the deductive method, facilitated infer criteria and get to organize the general problem of the research topic and relations based on individual circumstances; inductive method allowed extracting principles, laws, general rules and sustainable research, which went on to establish the specific findings of the investigation; the method of analysis and synthesis; This method was particularly important because it helped make the analysis and synthesis of the results and conclusions and present recommendations. The instruments used were the survey to people with physical disabilities Health Center and the Municipal Government of the canton Zapotillo Decentralized to see if they are included or excluded in your work, the second instrument was the Rosenberg Self-Esteem TEST applied to staff with disabilities, in order to assess the level of self-esteem. It is concluded that: 78% of people with disabilities if they have felt marginalized by their disabilities; 22% do not feel marginalized; 94% of people have not been given the opportunity to work in any public or private office, 6% have not had this opportunity; Also 50% of people said the factor by which have not been taken into account in society is by their disability; 11% responded that if there are such people in the Autonomous Municipal Government Zapotillo; It concludes that a single person with a disability working in an institution in the canton Zapotillo exist. 94% said that institutions if they have access ramps accessible to people with physical, disabilities are National Development Bank, Autonomous Municipal Government, Department of Health, CNT and the Chamber of Commerce Zapotillo; 36% of respondents are physically disabled used as technical assistance support arm; 31% wheelchairs; 14% support for two arms; 11% used orthopedic footwear; 5% and 3% prosthesis adapted cars.